Outcomes associated with antidepressant treatment according to the number of prescriptions and treatment changes: 5-year follow-up of a nation-wide cohort study - Ouazana-Vedrines, Charles; Lesuffleur, Thomas; Cuerq, Anne; Fagot-Campagna, Anne; Rachas, Antoine; Gastaldi-Ménager, Chrystelle; Hoertel, Nicolas; Limosin, Frédéric; Lemogne, Cédric; Tuppin, Philippe (Frontiers in Psychiatry, 2022)
Background Naturalistic studies regarding clinical outcomes associated with antidepressant treatment duration have yielded conflicting results, possibly because they did not consider the occurrence of treatment changes. This nation-wide population-based study examined the association between the number of filled prescriptions and treatment changes and long-term psychiatric outcomes after antidepressant treatment initiation. Methods Based on the French national health insurance database, 842,175 adults who initiated an antidepressant treatment in 2011 were included. Cox proportional-hazard multi-adjusted regression models examined the association between the number of filled prescriptions and the occurrence of treatment changes 12 months after initiation and four outcomes during a 5-year follow-up: psychiatric hospitalizations, suicide attempts, sick leaves for a psychiatric diagnosis, new episodes of antidepressant treatment. Results During a mean follow-up of 4.5 years, the incidence rates of the four above-mentioned outcomes were 13.49, 2.47, 4.57 and 92.76 per 1000 person-years, respectively. The number of filled prescriptions was associated with each outcome (adjusted HRs [95% CI] for one additional prescription ranging from 1.01 [1.00-1.02] to 1.10 [1.09-1.11]), as was the occurrence of at least one treatment change versus none (adjusted HRs [95% CI] ranging from 1.18 [1.16-1.21] to 1.57 [1.79-1.65]). Furthermore, the adjusted HRs [95% CI] of the number of filled prescriptions were greater in patients with (vs without) a treatment change for psychiatric hospitalizations (1.12 [1.11-1.14] vs 1.09 [1.08-1.10], p for interaction=0.002) and suicide attempts (1.12 [1.09-1.15] vs 1.06 [1.04-1.08], p for interaction=0.006). Limitations Lack of clinical data about the disorders warranting the prescriptions or their severity. Conclusions Considering treatment changes is critical when using administrative claims database to examine the long-term psychiatric outcomes of antidepressant treatments in real-life settings.